PEMBELAJARAN AKHLAK TASAWUF DAN PEMBENTUKAN KARAKTER MAHASISWA DI PERGURUAN TINGGI ISLAM - Sri Astuti A. Samad (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
Sufism values such as; patience, gratitude, qana'ah, and zuhud are formulas as well as a cure for the heart in wading life and increasingly global human life. Therefore, with the learning of Sufism learned by students, it is expected to have a psychological and social impact on his life not only on campus as an academic environment but also in the wider community. Thus the student will be able to contribute progressively because the values of Sufism have formed a good character. In this context also Islamic higher education will be able to become agents of change in society not only in the context of education and learning but also in character values that originate from the Islamic dimension, namely Sufism.